The risk of chlorpropham cross-contamination of grain in potato stores. (April 2019) - Douglas, Leisa; MacKinnon, Gillian; Cook, Gordon; Duncan, Harry; Briddon, Adrian; Seamark, Steven
Abstract: The contamination of food with pesticide residues is of significant concern to consumers and legislation has been implemented worldwide to ensure compliance with Maximum Residue Levels of chemicals in food. The occurrence of the potato sprout inhibitor, isopropyl N-(3-chlorophenyl) carbamate (chlorpropham or CIPC) residues on cereals, such as wheat, is of concern as this chemical is not authorised for use on cereals, and therefore the route of unintentional contamination warrants further investigation. This study reports on the risk of CIPC cross-contamination of grain that was stored in a commercial potato store and provides a method for low level quantification of CIPC in cereals. A High Performance Liquid Chromatography (HPLC UV/VIS) method for quantifying residues of CIPC in grains was successfully validated and the presence of CIPC was confirmed by Gas Chromatography Mass Spectrometry (GCMS). The magnitude of contamination in the grain was influenced by: (I) direct contact with the flooring of the store; (II) the headspace directly above the concrete surface and within the store itself and (III) contaminated dust/CIPC particles in the store atmosphere. Cross contamination is feasible irrespective of the CIPC concentrations in the concrete flooring and even with storage of grain at an elevated height above the concrete, suggesting that the route of cross contamination is a complex process involving physical and chemical (volatilization) factors. The results are significant for recommendations involving the storage of grain in buildings with a history of CIPC use and for remedial strategies for decontamination of these buildings. Highlights: CIPC cross contamination of grain occurs in potato stores. Contact with CIPC contaminated concrete contributes to cross contamination of grain. CIPC in the headspace within a store contributes to cross contamination. HPLC UV/VIS and GCMS were used to confirm CIPC contamination in grain.